Asset-Based Community Development: - Barid Nizarudin Wajdi, Muh; Ana Ferawati Ekaningsih, Lely; Syaiful Rizal, Hasan; Sa'adillah S.A.P. , Rangga; Fathurrohman, Amang (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This article explores Asset-Based Community Development (ABCD) through a bibliographic analysis, focusing on leveraging local strengths to empower communities. The study systematically reviews existing literature to assess how communities can effectively utilize their assets to address challenges, enhance social capital, and promote sustainable development. The analysis underscores the significance of community participation and highlights successful cases where the ABCD approach has led to long-term social change and resilience. The findings suggest that ABCD is a robust strategy for achieving sustainable community empowerment.